Prion protein monoclonal antibody (PRN100) therapy for Creutzfeldt–Jakob disease: evaluation of a first-in-human treatment programme. Issue 4 (April 2022) - Mead, Simon; Khalili-Shirazi, Azadeh; Potter, Caroline; Mok, Tzehow; Nihat, Akin; Hyare, Harpreet; Canning, Stephanie; Schmidt, Christian; Campbell, Tracy; Darwent, Lee; Muirhead, Nicola; Ebsworth, Nicolette; et al.
Summary: Background: Human prion diseases, including Creutzfeldt–Jakob disease (CJD), are rapidly progressive, invariably fatal neurodegenerative conditions with no effective therapies. Their pathogenesis involves the obligate recruitment of cellular prion protein (PrP C ) into self-propagating multimeric assemblies or prions. Preclinical studies have firmly validated the targeting of PrP C as a therapeutic strategy. We aimed to evaluate a first-in-human treatment programme using an anti-PrP C monoclonal antibody under a Specials Licence. Methods: We generated a fully humanised anti-PrP C monoclonal antibody (an IgG4 κ isotype; PRN100) for human use. We offered treatment with PRN100 to six patients with a clinical diagnosis of probable CJD who were not in the terminal disease stages at the point of first assessment and who were able to readily travel to the University College London Hospital (UCLH) Clinical Research Facility, London, UK, for treatment. After titration (1 mg/kg and 10 mg/kg at 48-h intervals), patients were treated with 80–120 mg/kg of intravenous PRN100 every 2 weeks until death or withdrawal from the programme, or until the supply of PRN100 was exhausted, and closely monitored for evidence of adverse effects. Disease progression was assessed by use of the Medical Research Council (MRC) Prion Disease Rating Scale, Motor Scale, and Cognitive Scale, and compared with that of untreated natural history controls (matched for disease severity, subtype, and PRNP codon 129 genotype) recruited between Oct 1, 2008, and July 31, 2018, from the National Prion Monitoring Cohort study. Autopsies were done in two patients and findings were compared with those from untreated natural history controls. Findings: We treated six patients (two men; four women) with CJD for 7–260 days at UCLH between Oct 9, 2018, and July 31, 2019. Repeated intravenous dosing of PRN100 was well tolerated and reached the target CSF drug concentration (50 nM) in four patients after 22–70 days; no clinically significant adverse reactions were seen. All patients showed progressive neurological decline on serial assessments with the MRC Scales. Neuropathological examination was done in two patients (patients 2 and 3) and showed no evidence of cytotoxicity. Patient 2, who was treated for 140 days, had the longest clinical duration we have yet documented for iatrogenic CJD and showed patterns of disease-associated PrP that differed from untreated patients with CJD, consistent with drug effects. Patient 3, who had sporadic CJD and only received one therapeutic dose of 80 mg/kg, had weak PrP synaptic labelling in the periventricular regions, which was not a feature of untreated patients with sporadic CJD. Brain tissue-bound drug concentrations across multiple regions in patient 2 ranged from 9·9 μg per g of tissue (SD 0·3) in the thalamus to 27·4 μg per g of tissue (1·5) in the basal ganglia (equivalent to 66–182 nM). Interpretation: Our academic-led programme delivered what is, to our knowledge, the first rationally designed experimental treatment for human prion disease to a small number of patients with CJD. The treatment appeared to be safe and reached encouraging CSF and brain tissue concentrations. These findings justify the need for formal efficacy trials in patients with CJD at the earliest possible clinical stages and as prophylaxis in those at risk of prion disease due to PRNP mutations or prion exposure. Funding: The Cure CJD Campaign, the National Institute for Health Research UCLH Biomedical Research Centre, the Jon Moulton Charitable Trust, and the UK MRC.